2016
DOI: 10.1186/s12882-016-0369-5
|View full text |Cite
|
Sign up to set email alerts
|

Long term evolution of endothelial function during kidney transplantation

Abstract: BackgroundEndothelial dysfunction is an important precursor to the development of atherosclerosis, and has been suggested to play a role in the increased cardiovascular risk in patients with end stage renal disease. Endothelial function improves rapidly following post kidney transplantation, but the long term change remains unclear. Hypothesizing that endothelial function would remain improved long term post kidney transplantation, we evaluated the longitudinal change of endothelial function, measured by flow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…First, we establish FMD as a stable prognostic marker of vascular health. Kensinger et al 28 showed that FMD improved 11 months after patients received a kidney transplant although this study was conducted from months 1 to 24 posttransplantation. However, the RTR participants in our cohort were assessed at a median of 7 (baseline) and 10 years (follow‐up) after transplantation.…”
Section: Discussionmentioning
confidence: 92%
“…First, we establish FMD as a stable prognostic marker of vascular health. Kensinger et al 28 showed that FMD improved 11 months after patients received a kidney transplant although this study was conducted from months 1 to 24 posttransplantation. However, the RTR participants in our cohort were assessed at a median of 7 (baseline) and 10 years (follow‐up) after transplantation.…”
Section: Discussionmentioning
confidence: 92%
“…[ 13 , 21 , 22 ] Likewise, a cross-sectional study showed significantly lower FMD values in KTRs than in dialysis subjects, [ 12 ] although a recent prospective study demonstrated stable FMD values between first and 24th month post-transplantation. [ 23 ] Furthermore, Sharma et al [ 24 ] reported significant FMD improvement after transplantation; however, the exact time-point of post-transplant FMD measurement was unknown. Finally, increased sympathetic nerve activity in KTRs was proven to be related to decreased distensibility of the muscular type arteries, which contributes to arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The association between oxidative stress, inflammation and CKD is well established ( Tucker et al, 2015 ). Although in humans, endothelial function improves after successful renal transplantation ( Kensinger et al, 2016 ), renal transplant recipients still have poor endothelial function in comparison to the healthy population ( Stadler et al, 2009 ). Immunosuppressant drugs undoubtedly contribute to this effect ( Ovuworie et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%